The Developing Bodily Self: How Posture Constrains Body Representation in Childhood. Issue 1 (7th August 2020) - Gottwald, Janna M.; Bird, Laura‐Ashleigh; Keenaghan, Samantha; Diamond, Clare; Zampieri, Eliana; Tosodduk, Haleema; Bremner, Andrew J.; Cowie, Dorothy
Abstract : Adults' body representation is constrained by multisensory information and knowledge of the body such as its possible postures. This study ( N  = 180) tested for similar constraints in children. Using the rubber hand illusion with adults and 6‐ to 7‐year olds, we measured proprioceptive drift (an index of hand localization) and ratings of felt hand ownership. The fake hand was either congruent or incongruent with the participant's own. Across ages, congruency of posture and visual–tactile congruency yielded greater drift toward the fake hand. Ownership ratings were higher with congruent visual–tactile information, but unaffected by posture. Posture constrains body representation similarly in children and adults, suggesting that children have sensitive, robust mechanisms for maintaining a sense of bodily self.